Safety and efficacy of four cycles of Brentuximab Vedotin as consolidation after autologous peripheral stem cell transplantation in relapsed/refractory Hodgkin lymphoma. Issue 7 (6th June 2020) - Kort, Jeries; Chidiac, Amanda; El Sayed, Rola; Massoud, Radwan; Nehme, Rita; Bazarbachi, Ali; El-Cheikh, Jean
Abstract: Brentuximab Vedotin (BV) is a chimeric anti-CD30 antibody, conjugated to anti-tubulin mono-methyl-auristatin. The AETHERA trial revealed increased PFS when BV is used as maintenance therapy for 16 cycles in high risk Hodgkin lymphoma (HL) after autologous stem cell transplantation (ASCT). However, this schedule is associated with high cost and significant toxicity. Our objective is to assess the safety and efficacy of four cycles Brentuximab Vedotin as consolidation after ASCT for relapsed/refractory (R/R) HL. We identified 20 consecutive adult patients with R/R HL treated with BV for four cycles as consolidation after ASCT. The indications for BV consolidation included primary refractory disease in 12 patients (60%), early relapse in 6 patients (30%) and extra-nodal involvement in two patients (10%). After a median follow up of 27 months, five (25%) patients relapsed. The median time to relapse was 6 months. Median PFS and OS were not reached. No significant toxicities were reported.